Si3O cluster： excited properties under external electric field and oxygen-deficient defect models - 徐国亮 刘雪峰 谢会香 张现周 刘玉芳 (Chinese physics B, 2011)
This paper investigates the excited states of Si3O molecule by using the single-excitation configuration interaction and density functional theory. It finds that the visible light absorption spectrum of Si3O molecule comprises the yellow and the purple light without external electric field, however all the visible light is included except the green light under the action of external electric field. Oxygen-deficient defects, which also can be found in Si3O molecule, have been used to explain the 1 from silicon-based materials but the microstructures of the materials are still uncertain Our results accord with the experimental values perfectly, this fact suggests that the structure of Si3O molecule is expected to be one of the main basic structures of the materials, so the oxygen-deficient defect structural model for Si3O molecule also has been provided to research the structures of materials.